Drought Scenario Analysis Using RiverWare: A Case Study in Urumqi River Basin, China - Shalamu Abudu; Zhuping Sheng; Hamed Zamani Sabzi; James Phillip King (Civil Engineering Journal, 2018)
In this study, we applied RiverWare modeling approach to evaluate the management decisions on surface water and groundwater diversions in the agricultural watershed of the Urumqi River Basin of Xinjiang in Northwestern China. A rule-based daily time step RiverWare model was developed to simulate the hydrologic effects of different water management alternatives considering irrigation and drainage systems, crop water use, and diversion rules at the diversion dams within the basin. Daily data period from 2005 to 2009 was used to calibrate the model and 2010-2012 was used to validate the model. A calibrated daily RiverWare model was then used to evaluate the management decisions under different drought scenarios that generated by using the snowmelt runoff model (SRM) that developed to simulate inflow from upstream of Yingxiongqiao gaging station. Two drought scenarios (reduced precipitation and increased temperature) analysis were performed, and the corresponding hydrological variables were compared to the baseline scenario. The results indicated that the model adequately reproduced the historical inflows for the Wulabo Reservoir. The scenario analysis results suggest that the reduced precipitation led to increased groundwater pumping for irrigation both in the spring and summer. The increased temperature induces a significant increase in surface runoff in the basin and leads to increased crop water demand within the irrigation district, and however does not necessarily reduce the groundwater pumpage. Water operation policies from RiverWare provide guidelines for conjunctive use of groundwater and surface water resources within the basin under different water supply scenarios in the future.